(untitled) (Journal of Plant Disease Sciences, 2026)
A roving survey was conducted during the season of 2023 in major chickpea rabi growing districts of Maharashtra, namely Ahilyanagar, Beed, Chhatrapati Sambhajinagar, Dharashiv, Hingoli, Jalna, Latur, Parbhani, Pune and Solapur, to assess the incidence of collar rot caused by . The mean disease Sclerotium rolfsii incidence across the surveyed districts was 12.73%. Among the surveyed locations, the highest disease incidence was recorded in Hingoli district (16.85%), followed by Parbhani and Jalna districts, whereas the lowest incidence was observed in Dharashiv district (8.62%). The variation in disease incidence among districts may be attributed to differences in soil type, cropping patterns, environmental conditions and management practices adopted by farmers. During the survey, infected chickpea plants showing typical symptoms such as yellowing, wilting and rotting at the collar region accompanied by white mycelial growth and mustard-sized sclerotia near the soil surface were observed. Representative infected plant samples were collected from different locations for pathogen isolation and further laboratory investigations. The association of collar rot incidence with black cotton soils and common cropping systems such as soybean–chickpea, pigeonpea–chickpea and urdbean–chickpea was evident, indicating that these agro-ecological conditions may favor disease development.